PECULARITIS OF COLLECTIVE IMAGES IN F.M. DOSTOEVSKY'S NOVEL “CRIME AND PUNISHMENT” (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-3-108-117 The author considers the collective images of bourgeoisie and officials in F.M. Dostoevsky's novel “Crime and Punishment”, largely determining the specificity of his artistic world. The relevance of the work is explained by the need for further study of Dostoevsky's character typology. The novelty of the study relates to the definition of the functions and specificity of the depiction of the class structure of society in the novel. The structure of the collective image is characterized, united by class nomination, static appearance and character, similarity of the plot role.Key words: F.M. Dostoevsky, “Crime and Punishment”, artistic world, bourgeoisie, officialdom, collective image